Evaluasi Kapasitas Tampung Sungai Konto Menggunakan Software HEC-RAS - Abidin, Zainal; Nugroho, Meriana Wahyu; Ramadhani, Rahma (PRODI D3 TEKNIK SIPIL, 2023)
The Konto River is an important river in East Java, Indonesia. It has its headwaters in the Argowayang-Anjasmoro Mountains in Malang District and flows northwest through Kediri District before emptying into the Brantas River in Jombang District. This river is a very important source of water, transportation, and agricultural land for the people of Jombang Regency and its surroundings. The purpose of this study is to determine the cross-sectional capacity of the downstream Konto River and reduce the impact of flooding on the surrounding community. The hydrological analysis used rainfall data from rain gauge stations STA Gudo, STA Bandar Kedungmulyo, and STA Perak to estimate the plan flood discharge. The results show that the Konto River embankment has an average area of 199.48 m² from STA 9+000 to 12+500, with a volume capacity of 718,138.00 m³.